The first laparoscopic resection of an aldosterone-secreting adrenocortical oncocytoma in a child - Melih Akin; Basak Erginel; Canan Tanik; Nurver Akinci; Abdullah Yildiz; Bahar Beker; Cetin Ali Karadag; Nihat Sever; Sebnem Turk; Ali Ihsan Dokucu (Elsevier, 2014)
Oncocytomas of the adrenal cortex are usually benign and nonfunctional, consisting of oncocytes in which the cytoplasm becomes eosinophilic due to the accumulation of abnormal mitochondria. Oncocytomas can exist in many organs and are frequently found in the salivary gland, kidneys, thyroid gland, parathyroid gland, and hypophysis. Functioning oncocytomas are very rarely observed in children, and no more than ten cases have been reported in the literature. Here, we present the first report of laparoscopic excision of an aldosterone-secreting adrenocortical oncocytoma in a child.